The differential diagnosis algorithm of ovarian tumors in reproductive patients: a prospective study - Natalia M. Podzolkova; Vasilii В. Osadchev; Kirill V. Babkov; Natalia E. Safonova (IP Berlin A.V., 2022)
Aim. The aim of the study was to evaluate the efficiency of different methods of preoperative diagnostics and to develop an algorithm for examining patients of reproductive age with ovarian tumors. Materials and methods. The study included 100 patients operated in the gynecological and oncogynecological departments of Pletnev State Clinical Hospital (Moscow) in the period from Sep 2019 to Dec 2020. The inclusion criteria were reproductive age (1840 years); unilateral/bilateral nature of ovarian lesion; ovarian tumor existing for at least 3 months and confirmed by the data of instrumental research methods; the size of the pathological formation of the ovary according to instrumental examination 30 mm; normal/elevated level of biochemical markers and diagnostic calculation indices: Carbohydrate Antigen 125 (СА 125), Carbohydrate Antigen 19-9, Carcinoembryonic Antigen, Human Epididymis protein 4 (HE4), Risk of Ovarian Malignancy Algorithm (ROMA), Risk of Malignancy Index (RMI). All patients underwent determination of the level of cancer markers CA 125 and HE4, followed by calculation of the RMI and ROMA indices for premenopause, gray scale ultrasound examination with Doppler blood flow assessment was performed. Next, a contrast-enhanced ultrasound examination (CEUS) was performed. Results. Sensitivity (Se) of the Ovarian-Adnexal Imaging-Reporting-Data System (O-RADS) in predicting tumor malignancy was 84.8% (95% confidence interval 95% CI 8088), specificity (Sp) 88.1% (95% CI 8591), accuracy (Acc) 0.86 (95% CI 0.820.90), odds ratio (OR) 41.18 (95% CI 21.080.7), area under the curve (AUC) 0.744. Se of CEUS in predicting malignancy was 90.9% (95% CI 8595), Sp 92.5% (95% CI 8997), Acc 0.92 (95% CI 0.880.96), OR 150.0 (95% CI 76.5294.0), AUC 0.895. Conclusion. Patients with O-RADS 2 are shown to be monitored by a gynecologist for 6 months with a control ultrasound examination once every 3 months. When O-RADS 3 criteria are identified, it is recommended to include the determination of cancer markers and surgical treatment in a gynecological hospital with subsequent morphological examination of the obtained material as a preoperative diagnosis. The identification of O-RADS 4 and O-RADS 5 criteria requires additional examination methods, such as the study of cancer markers (CA 125, HE4, ROMA, RMI), contrast-enhanced ultrasound (CEUS) and magnetic resonance imaging. CEUS showed high diagnostic efficiency in the presence of O-RADS 4 criteria, which made it possible to determine the necessary management tactics for patients with complex tumors. If the characteristics of the tumor are unclear, it is necessary to consider the possibility of surgical treatment in an oncological hospital.